À propos de l'algue fossile Marinella lugeoni PFENDER, 1939, nom. cons., et ses septs avatars malheureux. Révision de la Collection Juliette PFENDER. 2e partie. Révision de la Collection Jesse Harlan JOHNSON. 2e partie - Granier, Bruno [UNESP]; Dias-Brito, Dimas [UNESP] (Society for Sedimentary Geology, 2016)
A review of eight lookalike fossil species led to their being synonymized. Although Marinella lugeoni PFENDER, 1939, is not the senior synonym, it is proposed to ascribe it the status of a “nomen conservandum”. The age of its type-locality in Spain is Late Jurassic, not Early Jurassic. We also docu-ment small Marinella lumps found in Albian-Cenomanian strata of Brazil.
On the fossil alga Marinella lugeoni PFENDER, 1939, nom. cons., and its seven unfortunate avatars: Revision of the Juliette PFENDER collection. Part 2. revision of the jesse harlan JOHNSON collection. Part 2
Keywords: Elianellaceae; Marinella; Rhodogorgonales; Solenoporacea